Ten Years of Remote Sensing at Barcelona Expert Center (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book celebrates the ten-year anniversary of the Barcelona Expert Center by presenting recent contributions related to the topics on which the team has been working during these years. The Barcelona Expert Center expertise covers a wide variety of remote sensing fields, but the main focus of the research is on the Soil Moisture and Ocean Salinity (SMOS) data processing and its ocean, land, and ice applications. This book contains 14 scientific papers addressing topics that range from the description of the new data processing algorithms that are implemented in the last version of the operational SMOS Level 1 processor, to scientific applications derived from SMOS: results on the sea surface salinity assimilation in coastal models; synergies of the sea surface salinity with temperature and chlorophyll, and their impact on the better retrieval of ocean surface currents; quality assessment of SMOS derived sea ice thickness; sea surface salinity; and soil moisture products, among others. Moreover, one of the papers verifies the potential of the future CIMR mission within the CMEMS SSS operational production after the SMOS era.